National biodiversity planning : guidelines based on early experiences around the world (World Resources Insitue Hampden StationUS, 1995)
Explores the relationship among the three biodiversity-planning tools established by the convention viz country study, national strategy and action plan, as well as associated negotiations and resolutions. Analyses lessons learned from early experiences of seventeen countries. Presents a framework for national biodiversity planning using the Convention on Biological Diversity and identifies the specific actions needed. Lays out an illustrative biodiversity-planning process based on seven fundamnetal steps.
DC